Soluble receptor for advanced glycation end products and increased aortic stiffness in the general population - Mayer, Otto; Seidlerová, Jitka; Filipovský, Jan; Vágovičová, Petra; Wohlfahrt, Peter; Cífková, Renata; Windrichová, Jindra; Topolčan, Ondřej (Hypertension research, 2016)
It has been suggested that accumulation of advanced glycation end products (AGEs) is involved in several pathophysiological processes in the vessel wall. We hypothesized that low levels of the soluble receptor for AGEs (sRAGE) might be associated with increased arterial stiffness, a manifestation of vascular ageing in the general population. Using a cross-sectional design, we analyzed 1077 subjects from the Czech post-MONICA study. The aortic pulse wave velocity (aPWV) was measured using a Sphygmocor device. sRAGE concentrations were assessed in frozen samples using enzyme-linked immunosorbent assay methods (R&D Systems). aPWV significantly (P<0.0001) increased across the sRAGE quartiles. An aPWV of 1 m s(-1) was associated with a 37% increase in the risk of low sRAGE (<918 pg ml(-1), bottom quartile; P-value=0.018). In a categorized manner, subjects in the bottom sRAGE quartile had an odds ratio of an increased aPWV (⩾9.3 m s(-1)), adjusted for all potential confounders of 2.05 (95% confidence interval: 1.26-3.32; P=0.004), but this was only the case for non-diabetic hypertensive patients. In contrast, a low sRAGE was rejected as an independent predictor of an increased aPWV in normotensive or diabetic subjects using similar regression models. In conclusion, low circulating sRAGE was independently associated with increased arterial stiffness in a general population-based sample, but this was only observed in hypertensive non-diabetic patients.
Keywords: dospělí; Cross-Sectional Studies; Vascular Stiffness; tuhost cévní stěny; Humans; lidé středního věku; Middle Aged; aorta; Czech Republic; Receptor for Advanced Glycation End Products; Blood Pressure; mužské pohlaví; Česká republika; receptor pro konečné produkty pokročilé glykace; Adult; průřezové studie; krevní tlak; Pulse Wave Analysis; ženské pohlaví; analýza pulzové vlny; lidé; Aged; senioři; Male; Aorta; Female